"Not to Be Aware Anymore": Indigenous Sumatran Ideas and Shamanic Experiences of Changed States of Awareness/Consciousness. (26th March 2013) - Porath, Nathan
Abstract Anthropologists working on altered states of consciousness (ASC) have suggested that we should do away with psychologizing concepts and use people's own terms for these experiences. With material drawn from the Orang Sakai of Sumatra this paper shows that practitioners who utilize ASC do recognize the alteration of states of awareness as preconditions for numinous interactions. Also critically discussed is the term ASC.